An Evaluation of Resources Available to Learn About Orthopaedic Surgery Residency Programs. Issue 1 (22nd January 2023) - Malyavko, Alisa; Bernstein, Simone A.; Gu, Alex; Mulcahey, Mary K.
Abstract : Introduction: Orthopaedic surgery is one of the most competitive residencies to match into, and understanding what information is useful for applicants can reduce the number of programs applied to. The purpose of this study was to (1) determine which residency recruitment resources influence where applicants apply and how they rank programs, (2) identify what information would be most helpful for applicants to learn about programs, and (3) determine whether orthopaedic surgery applicants have preferential solutions to improve the application process. Methods: Medical students who applied to the orthopaedic surgery residency program at the senior author's institution during the 2021-2022 application cycle were invited to participate in this study. The anonymous Qualtrics survey covered several domains of demographics and questions about recruitment resources (e.g., residency websites, in-person away rotations, rankings, and databases with information about orthopaedic surgery programs). Results: Of the 216 survey respondents, 77 (35.6%) identified as female and 132 (61.1%) as male. Twenty-four (11.1%) respondents were the first in their family to graduate from an undergraduate program, and 47 (21.8%) applicants had a physician in their immediate family. Survey respondents selected in-person away rotations as the most influential factor in deciding where to apply (n = 97) and how to rank programs (n = 117). Regarding the residency match, 152 survey respondents (70.4%) would like interview caps, 128 (59.3%) would like an increase in program information available on residency databases, and 120 (55.5%) would like application caps. Discussion: Medical students applying to orthopaedic surgery residency programs found in-person away rotations to be most influential on which programs they applied to. Applicants would like more transparency during the application process to make better informed decisions when applying to and ranking programs. Residency program directors can apply these preferences to facilitate a more equitable process for all students applying to orthopaedic surgery. Level of Evidence: VI